COVID-19-Associated Pneumonia: Radiobiological Insights - François, Sabine; Helissey, Carole; Cavallero, Sophie; Drouet, Michel; Libert, Nicolas; Cosset, Jean-Marc; Deutsch, Eric; Meziani, Lydia; Chargari, Cyrus (Frontiers in Pharmacology, 2021)
The evolution of SARS-CoV-2 pneumonia to acute respiratory distress syndrome is linked to a virus-induced “cytokine storm”, associated with systemic inflammation, coagulopathies, endothelial damage, thrombo-inflammation, immune system deregulation and disruption of angiotensin converting enzyme signaling pathways. To date, the most promising therapeutic approaches in COVID-19 pandemic are linked to the development of vaccines. However, the fight against COVID-19 pandemic in the short and mid-term cannot only rely on vaccines strategies, in particular given the growing proportion of more contagious and more lethal variants among exposed population (the English, South African and Brazilian variants). As long as collective immunity is still not acquired, some patients will have severe forms of the disease. Therapeutic perspectives also rely on the implementation of strategies for the prevention of secondary complications resulting from vascular endothelial damage and from immune system deregulation, which contributes to acute respiratory distress and potentially to long term irreversible tissue damage. While the anti-inflammatory effects of low dose irradiation have been exploited for a long time in the clinics, few recent physiopathological and experimental data suggested the possibility to modulate the inflammatory storm related to COVID-19 pulmonary infection by exposing patients to ionizing radiation at very low doses. Despite level of evidence is only preliminary, these preclinical findings open therapeutic perspectives and are discussed in this article.